Endoscopy Assisted Oncoplastic Breast Surgery (EAOBS) - Gürsel Soybir; Eisuke Fukuma (European Journal of Breast Health, 2015)

(untitled)
Endoscopic oncoplastic breast surgery represents a minimal invasive approach with the aim of both removing cancer safely and also restoring the breast image. It has less noticeable scar, excellent cosmetic outcomes, high patient satisfaction rate and recently reported relatively long term safety. Operative techniques for both endoscopic breast conserving surgery and endoscopic nipple/areola/skin sparing mastectomy have been described in detail. Two different working planes in which one of them is subcutaneous and the other one is sub-mammary planes are being used during the surgery. Surgical techniqe needs some instruments such as endoscopic retractor, light guided specific mammary retractor, wound protector and bipolar scissor. Endoscopic breast retractors provide magnified visualization and extensive posterior dissection facility. Tunneling method and hydrodissection simplify the technique in the subcutaneous field. Oncoplastic reconstruction techniques are also applied after the tumor resection by endoscopic method. Complication rates of endoscopic breast surgery are similar to open breast surgery rates. Quite succesful local recurrence, distant metastasis and overall survival rates have been declared. However it looks reasonable to wait for the results with longer follow-up before having a judgement about oncologic efficiency and safety of the endoscopic breast cancer surgery.